2010
DOI: 10.1007/s10571-010-9585-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical and Biochemical Studies with Region-Specific Antibodies to Chromogranins A and B and Secretogranins II and III in Neuroendocrine Tumors

Abstract: This short review deals with our investigations in neuroendocrine tumors (NETs) with antibodies against defined epitopes of chromogranins (Cgs) A and B and secretogranins (Sgs) II and III. The immunohistochemical expression of different epitopes of the granin family of proteins varies in NE cells in normal human endocrine and non-endocrine organs and in NETs, suggesting post-translational processing. In most NETs one or more epitopes of the granins were lacking, but variations in the expression pattern occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
0
9
1
Order By: Relevance
“…Many reports have indicated that CgB is different from CgA in its level/mode of expression (30). In the present study, the correlation between serum CgB and CgA was not high, probably reflecting the difference in expression mechanisms between CgB and CgA.…”
Section: Discussioncontrasting
confidence: 84%
“…Many reports have indicated that CgB is different from CgA in its level/mode of expression (30). In the present study, the correlation between serum CgB and CgA was not high, probably reflecting the difference in expression mechanisms between CgB and CgA.…”
Section: Discussioncontrasting
confidence: 84%
“…Cg A was measured in these samples and in 125 patient with NEN samples using the Imperial Supra‐regional Assay Service radioimmunoassay (SAS) and three different commercial assays (Cisbio, DAKO, Eurodiagnostica). Samples were processed and analysed following manufacturer’s recommendations for each kit 9–11 …”
Section: Methodsmentioning
confidence: 99%
“…Samples were processed and analysed following manufacturer's recommendations for each kit. [9][10][11]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations